The Role of Fire in the Posthumous Customs of Podlachia on the Border of Poland and Belarus - Wawrzeniuk, Joanna (Studia mythologica Slavica, 2020)
In this article, I would like to describe the role of fire in the customs of All Souls’ Day in the Easter period called przewody or radunica. The burning of the fires most commonly took place overnight at home and in cemeteries to illuminate the way for the transmigration of souls so they would not harm the living. The reflection of special respect for fire is known from the funeral rites from the area of Podlachia in the Middle Ages. It also served as a basic element of the ritual related to cyclical visits to the dead, as evidenced by the remains of charcoals or ash. Different kind of sources from the Middle Ages and modern times, from the region of eastern Poland (Podlachia and Belarus, in particular) shall be used to confirm that the rite lasted for many years.